PENGARUH ZAT BERBAHAYA DALAM MAKANAN HARAM PERSPEKTIF AL-QUR’AN MENURUT WAHBAH ZUHAILI - Ihwan Agustono; Obey Destine Najiha (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2022)
Some imported and exported food products are doubtful because they do not meet the halal certification requirements. Unfortunately, some Indonesia still consume food with no-halal certificate due to a lack of information that packaged food products must receive halal certification. Halal assessment through halal certification is very crucial as a halal guarantee from authoritative parties. In addition, the halal status of the food consumed affects the human soul. This research employs a descriptive analysis method using Tafsir Munir as a primary source. The results show, according to Wahbah Zuhaili, that there is an influence of haram food in human life from various aspects. Food ingredients will affect aspects of human health, morals, and religion. When food intake is good, all aspects of life are good, and vice versa. Unless the group of people whom Allah has given an exception, those who are in an exigent situation where there is no other choice but to consume haram food.